DAMPAK MODAL KERJA, STRUKTUR MODAL, STRUKTUR ASET, LIKUIDITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS (Studi Empiris Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Aprillia Zustika Sari Zustika; Mohammad Ghofirin, S.Pd., M.Pd. Mohammad Ghofirin (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
The purpose of this research is to analyze the effect of Working Capital, Capital Structure, Asset Structure, Liquidity, and Company Growth on Profitability (Empirical Study of Food and Beverage Companies Listed on the IDX). The information used in this research is secondary information, taken from the 2014-2018 annual financial reports of the Food & Beverage Industry listed on the Indonesia Stock Exchange. The sampling method used was purposive sampling. The research sample consisted of 11 companies that entered the research standards in 2014-2018. The results of this study indicate that partially working capital has a positive effect on profitability, capital structure has a negative effect on profitability, asset structure has a positive effect on profitability, liquidity has a negative effect on profitability, and company growth has no effect on profitability. Simultaneously, the variables of working capital, capital structure, asset structure, liquidity, and company growth have an effect on profitability. Keywords: Working Capital, Capital Structure, Asset Structure, Liquidity,Company Growth, Profitability.